If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2p + 5q = -53 Solving 2p + 5q = -53 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-5q' to each side of the equation. 2p + 5q + -5q = -53 + -5q Combine like terms: 5q + -5q = 0 2p + 0 = -53 + -5q 2p = -53 + -5q Divide each side by '2'. p = -26.5 + -2.5q Simplifying p = -26.5 + -2.5q
| 8x+12y=50 | | 9(10m+7)=9(8m+9) | | 5x+4=x+2 | | -9=-8+x | | 4.6x+2.2=29.8 | | 3.9=1.3-(4y) | | B=T-LcsolveT | | 14=7(x-1) | | 8x+4x-76=95-7x | | 5r+6r+7r-6= | | -0.01+0.1+(-1)+10= | | 5p+5=4p+12 | | 4t^2-24t-1=0 | | 3x+12=2x+72 | | 2(x+1)=10-2 | | 7x+146+x+48+65=65 | | 3+4-2+(8-5)= | | 3x-11=-33 | | t^2+16=8r | | -15+n=-25 | | 5x(12)-22+8x+46=180 | | 7e+3p+4p-5x+6= | | 1.9=-0.2 | | 5m-9n-6m=9n | | 29-4=-7(3x+8) | | 3x-2+19=180 | | x-(-2)=14 | | 7e+3p+4p-x+6= | | 15-4(3-x)=12+15x | | 14x-(3x-2)=90 | | 3.9=1.3-.4y | | x^2-sqrt(6)x+4=0 |